2008
DOI: 10.2478/v10033-008-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Leadership Styles on Employees' Organizational Commitment in Lithuanian Manufacturing Companies

Abstract: Abstract:This article investigates the relationship between employees' organizational commitment dimensions and leadership styles in Lithuanian manufacturing companies. The findings of the study reveal positive correlations between a transformational leadership style and affective and normative employee commitments. A laissez-faire leadership style was found to be negatively associated with employees' affective commitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 30 publications
13
34
0
Order By: Relevance
“…According to the results of hierarchical regression analysis, only transformational leadership had a significant effect on coaches' satisfaction, effectiveness, and extra effort. The result of Chiun et al 2009and Buciuniene and Skudiene's (2008) research indicated that transformational leadership had a significant positive effect on organizational commitment and transactional leadership has no significant effects on organizational commitment (Chiun et al, 2009). Passive-avoidant leadership had a negative and significant relationship with employees' affective and normative commitment and doesn't have any significant correlation with continuance commitment (Buciuniene and Skudiene, 2008).…”
Section: Direct Effects Of Leadership Styles On Organizational Effectmentioning
confidence: 99%
“…According to the results of hierarchical regression analysis, only transformational leadership had a significant effect on coaches' satisfaction, effectiveness, and extra effort. The result of Chiun et al 2009and Buciuniene and Skudiene's (2008) research indicated that transformational leadership had a significant positive effect on organizational commitment and transactional leadership has no significant effects on organizational commitment (Chiun et al, 2009). Passive-avoidant leadership had a negative and significant relationship with employees' affective and normative commitment and doesn't have any significant correlation with continuance commitment (Buciuniene and Skudiene, 2008).…”
Section: Direct Effects Of Leadership Styles On Organizational Effectmentioning
confidence: 99%
“…To date, many different definitions for this concept have been suggested (Buciuniene & Skudiene, 2008;Fields, 2002), and the reason for this is that it has a multi-dimensional structure that includes the attitude and behavioral components of commitment to work (Meyer, Allen, & Smith, 1993). In one study, organizational commitment was defined as the strength of an employee's identification with the organization (Porter, Steers, Mowday, & Boulian, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Besides,Bučiūnienė & Škudienė (2008) reveal positive associations between transformational leadership and normative and affective employee commitments. What's more, by using a longitudinal examination byHill &et al(2012), the result exhibits that the transformational leadership style distinctly sways employees' normative commitment to change and employees' affective commitment to change.…”
mentioning
confidence: 87%